The Coaching Achievement Evaluation of the Archery at Bakorwil III Central Java in 2021 - Wardani, Vera Eka; Hanani, Endang Sri; Hartono, Mugiyo (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
Those problems are the training program is not textual, the funding is limited, and the facilities and infrastructure are not complete.The objectives of this research are to analyze: 1) the antecedent ofthe archery achievement development; 2) the transaction of the archery achievement development; 3) the outcome of archery achievement development. This research employs qualitative approach and applies evaluation model, namely antecedent, transaction, and outcome. The sources of the research data are administrators, coaches, athletes, and documentation in the form of coachinglicenses and data of thePerpani’s administrators. The data were collected through observation, interviews, and documentation. These data were analysed using data collection, data reduction, data presentation, and drawing conclusions. The results of the antecedent evaluation on the archery achievement development showed that: 1) the training program arrangement was made textually,the success of the program had not been fulfilled; and 2) the organizational structure was carried out according to the duties and responsibilities. The transaction evaluation showed that: 1) the enrolment of the athletes was carried out without any selection; 2) the coaches were appointed by the administrators,; 3) the source of funds came from KONI, sponsorships, and parents of the athletes; 4) the availability of infrastructure is still limited. The outcome evaluation showed that the Perpani Pati's achievement is at the national level, the Kudus's achievement isat the national open championships, the Jepara's achievement is atthe national championships, and the Grobogan's achievement is at the international championship. It can be concluded that the facilities and infrastructure needs to get renewed.